A 4-year prospective investigation of predictive effects of prepandemic sexual stigma, affective symptoms, and family support on fear of COVID-19 among lesbian, gay, and bisexual individuals - Huang, Mei-Feng; Chang, Yu-Ping; Chou, Wen-Jiun; Yen, Cheng-Fang (Frontiers in Public Health, 2024)
The aim of this 4-year prospective study was to evaluate the predictive effects of prepandemic sexual stigma, depression, anxiety, and perceived family support on fear of coronavirus disease 2019 (COVID-19) among young adult lesbian, gay, and bisexual (LGB) individuals. Methods: Data on prepandemic demographics, three types of sexual stigma, depression, anxiety, and perceived family support were collected from 1,000 LGB individuals between August 2018 and June 2019. The fear of COVID-19 was surveyed again after 4 years. The associations of prepandemic sexual stigma, depression, anxiety, and perceived family support on fear of COVID-19 at follow-up were analyzed through linear regression.Results: In total, 673 (67.3%) participants completed the follow-up assessment. After adjustment for demographic characteristics, greater prepandemic perceived sexual stigma from family members (p = .001), internalized sexual stigma (p < .001), sexual orientation microaggression (p < .001), and higher levels of prepandemic depression (p < .001) and anxiety (p < .001) were significantly associated with a greater fear of COVID-19 at follow-up. Prepandemic perceived family support was not significantly associated with the fear of COVID-19 (p = .785).The identified predictors should be considered when designing interventions aimed at reducing the fear of COVID-19 in LGB individuals.